2023
DOI: 10.1200/cci.22.00104
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives on Barriers and Enablers to Implementing an Inpatient Oncology Early Warning System: A Mixed-Methods Study

Abstract: PURPOSE To elicit end-user and stakeholder perceptions regarding design and implementation of an inpatient clinical deterioration early warning system (EWS) for oncology patients to better fit routine clinical practices and enhance clinical impact. METHODS In an explanatory-sequential mixed-methods study, we evaluated a stakeholder-informed oncology early warning system (OncEWS) using surveys and semistructured interviews. Stakeholders were physicians, advanced practice providers (APPs), and nurses. For qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Compounding these failures are general and cancer-specific implementation barriers. Lyons et al found that key design and deployment challenges are magnified in the highlyspecialized cancer care setting [138][139][140][141]. Without effective information displays, workflows, and strategies for implementation, predictive information is ignored in an environment where alerts are ubiquitous, untimely, and workflow-misaligned.…”
Section: Time Is Of the Essence: Facilitating Early Recognition And M...mentioning
confidence: 99%
“…Compounding these failures are general and cancer-specific implementation barriers. Lyons et al found that key design and deployment challenges are magnified in the highlyspecialized cancer care setting [138][139][140][141]. Without effective information displays, workflows, and strategies for implementation, predictive information is ignored in an environment where alerts are ubiquitous, untimely, and workflow-misaligned.…”
Section: Time Is Of the Essence: Facilitating Early Recognition And M...mentioning
confidence: 99%